Pseudotetracha timberensis: a new species from the Northern Territory, Australia (Coleoptera: Carabidae, Cicindelinae, Megacephalini) and considerations on the taxonomy of Pseudotetracha - Häckel, Martin; Anichtchenko, Alexandr (Zootaxa, 2015)
A new species of Pseudotetracha from Northern Territory, Australia, is described and compared with Pseudotetracha marginicollis (Sloane, 1906). The position of the species in the genus and the subgeneric classification of Pseudotetracha Fleutiaux, 1894 are discussed. It is proposed that the genus would be divided into the following species groups: “australasiae”, “australis”, “blackburni”, “crucigera”, “cylindrica”, “greyana” and “marginicollis”.